The principle of accountability for the object of the auction held - Abdul Majid; Habib Adjie (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2022)
This study aims to determine the principles of accountability owned by PT Balai Lelang Serasi. This study uses a normative juridical approach. The data collection technique used is documentation technique (literature study and scientific journal articles). The data analysis technique used is descriptive and critical analysis. The results of this study indicate that the principle of accountability owned by PT Balai Lelang Serasi can be seen from the provision of access to prospective bidders to check the physical condition and completeness of the auction object documents at the open house stage; obliges the prospective bidder to pay a security deposit which will later be returned to the bidder in accordance with what is stated on the registration form (auction participants must deposit a security deposit of Rp 5,000,000 (five million rupiah)/car and auction list as proof of commitment that the prospective bidder guarantees that he or she is willing to participate in the auction); and the auction winner is fully responsible for what he bids, and he wins.